Combined effects of prolonged temperature and hypoxia stress on growth, metabolism and physiological status of yellow catfish (Pelteobagrus fulvidraco) - Jie Wang; Liang Li; Shasha Zhao; Man Wang; Bo Li; Hongxi Guo; Dong Han; Xiaoming Zhu; Lei Zhang (Aquaculture Reports)
Temperature and dissolved oxygen concentration are critical to fish. This study analyzed the effects of prolonged temperature and dissolved oxygen stress on growth metabolism, oxidative stress, immunity, and apoptosis in yellow catfish (Pelteobagrus fulvidraco). To this end, yellow catfish were continuously exposed to three temperatures (15, 26, and 32 °C) and two dissolved oxygen concentrations (2.5 and 6.5 mg/L) for 28 days. Notably, unsuitable temperatures and hypoxic exposure significantly decreased growth parameters (final body weight, weight gain, and specific growth rate), decreased survival rate, and significantly decreased crude protein and crude lipid in muscle (p < 0.05). Further, the serum glucose content was reduced, lactate dehydrogenase activity and lactic acid content were increased, and the activities of key glycolysis enzymes (hexokinase, pyruvate kinase, and phosphofructokinase) were significantly elevated (p < 0.05). Notably, prolonged temperature and dissolved oxygen stress triggered oxidative stress in yellow catfish, as evidenced by a significant increase in malondialdehyde content in serum and gills (p < 0.05), elevated levels of antioxidant enzyme activity and expression (superoxide dismutase, catalase, and glutathione peroxidase), and damaged gills and head kidney tissues. In addition, the expression of immuno-inflammatory factors and apoptotic genes (c3-like, tnfaip2, il-1β, caspase-3 and caspase-9) was significantly increased (p < 0.05) in the head kidney of the yellow catfish. Our findings showed that combined long-term temperature and dissolved oxygen stress have complex effects on fish, with the growth performance of yellow catfish at 32 °C more susceptible to hypoxia stress than at 15 °C. Collectively, these findings elucidate the response mechanism of fish to long-term temperature and dissolved oxygen stress and provide a theoretical resource to guide the healthy aquaculture of aquatic products.